Peningkatan Minat dan Hasil Belajar Matematika Melalui Model TGT Berbantuan Papan Dakota pada Siswa Kelas V SDN Sumurboto - Sri Sya'adah, Meila; Teguh Purnawanto, Ahmad; Nurwulandari, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was inspired by the low interest and mathematics achievement of fifth-grade students at SDN Sumurboto on the topics of LCM and GCD. The research aimed to improve students’ learning interest and achievement through the Teams Games Tournament (TGT) cooperative learning model assisted by Dakota Board media. This research used Classroom Action Research based on the Kemmis and McTaggart model conducted in two cycles. The subjects were 15 students, and data were collected through observation, questionnaires, interviews, tests, and documentation. The findings showed that students’ learning interest and mathematics achievement improved in each cycle. The average interest score increased from 23.5 in the pre-cycle to 32.33 in Cycle II, while the average learning outcome score improved from 67.2 to 82.67. Classical mastery also increased from 46.67% to 93.33%. These results show that the TGT model assisted by Dakota Board media effectively improved students’ interest and mathematics learning outcomes.